2023
DOI: 10.1097/pcc.0000000000003262
|View full text |Cite
|
Sign up to set email alerts
|

Caring for Critically Ill Children With the ICU Liberation Bundle (ABCDEF): Results of the Pediatric Collaborative*

Abstract: OBJECTIVES: Assess clinical outcomes following PICU Liberation ABCDEF Bundle utilization. DESIGN: Prospective, multicenter, cohort study. SETTING: Eight academic PICUs. PATIENTS: Children greater than 2 months with expected PICU stay greater than 2 days and need for mechanical ventilation (MV). INTERVENTIONS: ABCDEF Bundle implementation. MEASUREMENT AND MAIN RESULTS: Over an 11-month period (3-mo baseline, 8-mo implementation), Bundle utilization was measured for 622 patients totaling 5,017 PICU day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The study by Choong et al (5) focused on assessing the adherence to bundle utilization in ventilated pediatric patients. While they did note an increased utilization of the bundle, they did not find any associations with mechanical ventilation duration, PICU length of stay, or the presence of delirium, in contrast to findings in adult patients (14, 15). Unexpectedly, upon conducting adjusted analyses, enhanced bundle utilization correlated with a decreased probability of death.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…The study by Choong et al (5) focused on assessing the adherence to bundle utilization in ventilated pediatric patients. While they did note an increased utilization of the bundle, they did not find any associations with mechanical ventilation duration, PICU length of stay, or the presence of delirium, in contrast to findings in adult patients (14, 15). Unexpectedly, upon conducting adjusted analyses, enhanced bundle utilization correlated with a decreased probability of death.…”
mentioning
confidence: 68%
“…A study conducted in adult ICUs has revealed that the complete implementation of the ABCDEF bundle is linked to improved survival rates, as well as reduced durations of mechanical ventilation, delirium, and coma (13). Recently, the results of a multicenter study on the clinical outcomes following the application of the Pediatric ABCDEF bundle were published (14). The study by Choong et al (5) focused on assessing the adherence to bundle utilization in ventilated pediatric patients.…”
mentioning
confidence: 99%
“…The unexpected lack of significant differences between the groups may also be attributed, in part, to the rehabilitation/early mobility program and implementation of the ABCDEF Bundle (37–39) as well as strong psychosocial and behavioral health services provided to patients within this institution. In 2022, the PICU Core Outcome Measurement Set forth core measures to study PICU outcomes to facilitate continued research for post-PICU patients and survivors, including cognitive, emotional, and social health (40).…”
Section: Discussionmentioning
confidence: 99%
“…7 In a multicenter study of 622 high-risk pediatric ICU (PICU) patients, a concerted Pediatric ICU Liberation implementation effort modestly improved ABCDEF Bundle element adoption from 50% to 64% over an 8-month period. 8 Unfortunately, this increase was not sufficient to be associated with improved MV duration, delirium, or ICU length of stay. An international survey of 161 PICUs in 18 countries reports that ABCDEF Bundle components have been variably adopted worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Seattle Children's Hospital (SCH) was one of eight pediatric institutions that participated in the PICU Liberation implementation study. 8 As part of that work, we developed and conducted a PICU staff survey study to understand what barriers were perceived or experienced in implementing ABCDEF Bundle elements. We conducted this survey in 2017 and again in 2020, and used staff responses to identify the most common barriers, examine changes in barrier perception over time, and examine differences in barrier perception by role, to inform our local implementation efforts.…”
Section: Introductionmentioning
confidence: 99%